Magneto‐Structural and Computational Study of a Tetranuclear Copper Complex Displaying Carbonyl–π Interactions. Issue 47 (10th December 2018) - Kochem, Amélie; Faure, Bruno; Bertaina, Sylvain; Rivière, Eric; Giorgi, Michel; Réglier, Marius; Orio, Maylis; Simaan, A. Jalila
Abstract: Invited for the cover of this issue is Dr. Maylis Orio from the University of Aix Marseille, France. The cover image shows a tetranuclear complex with four copper(II) ions bridged by alkoxo linkers. Abstract : The combination of experimental and theoretical data suggest that intramolecular noncovalent interactions contribute to the stabilization of the unusual distorted metal-oxo core and are probably important to drive the aggregation process … Read more about the story behind the cover in the Cover Profile and about the research itself in theFull Paper by M. Orio, A. J. Simaan et al.